Enhancing bio-butanol production from biomass of Chlorella vulgaris JSC-6 with sequential alkali pretreatment and acid hydrolysis. (January 2016) - Wang, Yue; Guo, Wanqian; Cheng, Chieh-Lun; Ho, Shih-Hsin; Chang, Jo-Shu; Ren, Nanqi
Highlights: Efficient butanol production was achieved by using carbohydrate-rich microalgae. Sequential alkali/acidic treatment on microalgae could produce fermentable sugars. The effects of biomass loading and acid/base concentration on hydrolysis were studied. Possible proteineous inhibitors originating from microalgal biomass were reported. Abstract: This study presents a successful butanol production method using alkali and acid pretreated biomass of Chlorella vulgaris JSC-6. The butanol concentration, yield, and productivity were 13.1 g/L, 0.58 mol/mol sugar, 0.66 g/L/h, respectively. Nearly 2.93 L/L of biohydrogen was produced during the acidogenesis phase in ABE fermentation. The hydrogen yield and productivity were 0.39 mol/mol sugar and 104.2 g/L/h respectively. In addition, the high glucose consumption efficiency (97.5%) suggests that the hydrolysate pretreated with NaOH (1%) followed by H2 SO4 (3%) did not contain inhibitors to the fermentation. It was also discovered that an excess amount of nitrogen sources arising from hydrolysis of highly concentrated microalgal biomass negatively affected the butanol production. This work demonstrates the technical feasibility of producing butanol from sustainable third-generation feedstock (i.e., microalgal biomass).